Coffee Supply Chain in West Sumatra: A Systematic Literature Review - Saputra, Hendra; Yunita, Imelda; Rozalia, Rozalia; Salim, Emil (LPPM Universitas Andalas, 2025)
This systematic literature review explores the coffee supply chain in West Sumatra, a region renowned for its strong agricultural heritage and substantial coffee production. The study aims to synthesize previous research and identify key factors influencing the supply chain stages—production, processing, marketing, and distribution. Using a structured methodology based on systematic review protocols, this research integrates findings from various academic sources to provide a comprehensive understanding of the topic. The reviewed literature reveals both challenges and opportunities within the West Sumatran coffee supply chain. Major challenges include post-harvest quality management, limited market access, and low adoption of sustainable practices, all of which affect competitiveness. The findings highlight the importance of effective governance and stakeholder collaboration in improving operational efficiency and market adaptability. Additionally, technological innovation and digital marketing are recognized as crucial in transforming the supply chain, supporting smallholder farmers, and expanding market reach. Overall, this review underscores the complexity and significance of West Sumatra’s coffee supply chain, emphasizing the need for integrated, sustainable, and innovative strategies to strengthen resilience and global competitiveness.